Influencias institucionales y pedagógicas del contexto escolar en la elección de carrera de estudiantes de grado once - Lizcano, Catalina (Revista Científica, 2011)
This communication is derived from the partial report of the Thesis of Masters in Pedagogic of the University of the Savannah with the title: Institutional and Pedagogical influences of the Scholastic Context in the Election of Race of Students of Degree 11, where are investigated Which are Influences Institutional and Pedagogical that allows the eleven student of degree of an Educative Institution of Bogota to construct their option of race?